Academically Resilient, Low-Income Students' Perspectives of how School Counselors Can Meet their Academic Needs. (2016) - Joseph, Williams; Sam, Steen; Albert, Tracy; Dely, Betty; Jacobs, Brian; Nagel, Chelsea; Irick, Anese
This phenomenological, qualitative study examined a national sample of academically resilient, low-income middle school students' (N = 24) perspectives of what school counselors can do to promote their academic achievement. Three main themes and nine subthemes were identified: build meaningful relationships, build on the cultural wealth of students, and provide mental health services in schools. This article discusses implications for school counselor practice and future research.